2004
DOI: 10.1038/sj.onc.1207022
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of human osteopontin promoter by C/EBPα and AML-1 in metastatic cancer cells

Abstract: Osteopontin (OPN) is a secreted glycoprotein produced by osteoclasts, macrophages, T cells, hematopoietic cells, and vascular smooth muscle cells. It contributes to macrophage homing and cellular immunity. It also mediates neovascularization, inhibits apoptosis, and plays important roles in extracellular matrix remodeling and angiogenesis. These properties are also characteristics of metastatic cancer cells. Consequently, the OPN gene was found to be upregulated among various metastatic cancer cells. This sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 38 publications
3
30
0
1
Order By: Relevance
“…Other transcription factors could regulate OPN expression in myeloma cells given that a transcriptional regulation of OPN promoter by C/EBPa and to a minor extent by AML-1 in metastatic cancer cells has recently been demonstrated. 12 In this study, we have tested C/EBPa mRNA expression in several HMCLs but we failed to detect it, demonstrating that C/EBPa is not involved in OPN production by myeloma cells. On the other hand, we found that myeloma cells express the two major isoforms of the transcription factor AML-1, AML-1A and AML-1B, as previously described, 38 even if any correlation between OPN expression and AML-1 expression or AML-1A/AML-1B ratio has not been found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other transcription factors could regulate OPN expression in myeloma cells given that a transcriptional regulation of OPN promoter by C/EBPa and to a minor extent by AML-1 in metastatic cancer cells has recently been demonstrated. 12 In this study, we have tested C/EBPa mRNA expression in several HMCLs but we failed to detect it, demonstrating that C/EBPa is not involved in OPN production by myeloma cells. On the other hand, we found that myeloma cells express the two major isoforms of the transcription factor AML-1, AML-1A and AML-1B, as previously described, 38 even if any correlation between OPN expression and AML-1 expression or AML-1A/AML-1B ratio has not been found.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, other transcription factors may also be involved in the production of OPN by cancer cells as the CCAAT/enhancerbinding protein alpha (C/EBPa) and AML-1, because it has been demonstrated that OPN promoter contains their DNA binding consensus regions. 12 OPN interacts with CD44 as a major receptor promoting cell adhesion, proliferation and survival. 7,13 Recent data indicate that OPN also stimulates endothelial cell survival and migration [13][14][15] and acts as a potent proangiogenic factor in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, co-immunoprecipitation revealed direct association of Myc and C/EBP proteins in MC29-transformed cells. C/EBPa is a multifunctional transcription factor that is involved in the specification of the differentiated phenotype through gene activation, but was recently also implicated in the acceleration of cell proliferation and activation of metastasis related genes (Heckman et al, 2003;Liu et al, 2004;Wang and Timchenko, 2005). Notably, functional interactions of Myc with the C/EBPb protein have been reported previously (Mink et al, 1996;Hartl et al, 2003).…”
Section: Ws5 a Direct Transcriptional Target Of Myc F Reiter Et Almentioning
confidence: 99%
“…Several known cis-acting transcription factors have been described and most of them have been localized to a conserved region at 250 bp upstream of the proximal promoter. Potential binding sites for transcriptional regulators, such as AP-1, Myc, Oct-1, USF, v-Src, TGF-b/BMPs/Smad/Hox, Wnt/ b-catenin/APC/GSK-3b/Tcf-4, Ras/RRF, TF53, Runx2, and ETS family members, have been identified (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%